Is the Immunological Response a Bottleneck for Cell Therapy in Neurodegenerative Diseases? - Salado-Manzano, Cristina; Perpiña, Unai; Straccia, Marco; Molina-Ruiz, Francisco J.; Cozzi, Emanuele; Rosser, Anne E.; Canals, Josep M. (Frontiers in Cellular Neuroscience, 2020)
Neurodegenerative disorders such as Parkinson’s (PD) and Huntington’s disease (HD) are characterized by a selective detrimental impact on neurons in a specific brain area. Currently, these diseases have no cures, although some promising trials of therapies that may be able to slow the loss of brain cells are underway. Cell therapy is distinguished by its potential to replace cells to compensate for those lost to the degenerative process and has shown a great potential to replace degenerated neurons in animal models and in clinical trials in PD and HD patients. Fetal-derived neural progenitor cells, embryonic stem cells or induced pluripotent stem cells are the main cell sources that have been tested in cell therapy approaches. Furthermore, new strategies are emerging, such as the use of adult stem cells, encapsulated cell lines releasing trophic factors or cell-free products, containing an enriched secretome, which have shown beneficial preclinical outcomes. One of the major challenges for these potential new treatments is to overcome the host immune response to the transplanted cells. Immune rejection can cause significant alterations in transplanted and endogenous tissue and requires immunosuppressive drugs that may produce adverse effects. T-, B-lymphocytes and microglia have been recognized as the main effectors in striatal graft rejection. This review aims to summarize the preclinical and clinical studies of cell therapies in PD and HD. In addition, the precautions and strategies to ensure the highest quality of cell grafts, the lowest risk during transplantation and the reduction of a possible immune rejection will be outlined. Altogether, the wide-ranging possibilities of advanced therapy medicinal products (ATMPs) could make therapeutic treatment of these incurable diseases possible in the near future.